2009
DOI: 10.1007/s00535-009-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Present status and strategy of NSAIDs-induced small bowel injury

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are well known to cause gastroduodenal mucosal lesions as an adverse effect. Recently, the serious problem of NSAID-induced small intestinal damage has become a topic of great interest to gastroenterologists, since capsule endoscopy and balloon enteroscopy are available for the detection of small intestinal lesions. Such lesions have been of great concern in clinical settings, and their treatment and prevention must be devised as soon as possible. The prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
183
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(201 citation statements)
references
References 78 publications
8
183
0
10
Order By: Relevance
“…Our results indicated that the incidence of small intestinal mucosal injury tended to be lower in Hp-infected patients than in non-Hp-infected patients. Because aspirin or NSAIDs inhibit cyclooxygenase (COX) and prostaglandin (PG) production at inflamed sites and may increase the risk of mucosal damage in the small intestine [18,19], the incidence of enteritis was determined in patients not receiving aspirin/NSAIDs; the results of this evaluation revealed that the rate of enteritis was significantly lower in the Hp-infected patients than in the Hp-noninfected patients. These findings suggest that H. pylori infection might protect the small intestinal mucosa against injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that the incidence of small intestinal mucosal injury tended to be lower in Hp-infected patients than in non-Hp-infected patients. Because aspirin or NSAIDs inhibit cyclooxygenase (COX) and prostaglandin (PG) production at inflamed sites and may increase the risk of mucosal damage in the small intestine [18,19], the incidence of enteritis was determined in patients not receiving aspirin/NSAIDs; the results of this evaluation revealed that the rate of enteritis was significantly lower in the Hp-infected patients than in the Hp-noninfected patients. These findings suggest that H. pylori infection might protect the small intestinal mucosa against injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that both isoforms of the COX enzyme (COX-1 and COX-2) play a role in maintaining mucosal integrity of the small intestine. 3 The microcirculatory dysfunction and increase in intestinal motility noted with the use of NSAIDs may also play a contributory role in the development of NSAID-induced enteropathy. 3 Complications NSAID-induced enteropathy often goes undetected because patients are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…3 The microcirculatory dysfunction and increase in intestinal motility noted with the use of NSAIDs may also play a contributory role in the development of NSAID-induced enteropathy. 3 Complications NSAID-induced enteropathy often goes undetected because patients are asymptomatic. Increased intestinal permeability has been reported to occur as early as 12 hours after a single dose of most conventional NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to internal and external inflammation in tissues, organs etc. There are well established anti-inflammatory synthetic drugs, which help as pain killer as well as recovery of swelling in tissues however, may cause side effect like ulcer in gastrointestinal tract [33][34][35][36][37]. Moreover, aqueous flower extract of C. procera has been documented to arrest pain, fever and inflammation [38][39] while ethanolic extract of root bark showed anti-inflammatory properties without any side effect [9,40].…”
Section: Introductionmentioning
confidence: 99%